A Study on the Perception of Environment and Developing Cognitive Maps - (:unkn) unknown (MARMARA UNIV, 2017)
This study is conducted in purpose of developing children's environmental perceptions about their surroundings and their reflection to children's cognitive mappings and correcting, if there are any, fallacies about their surroundings they live in. During this study case analysis's method is utilized among the qualitative research methodologies. Sketches about school and its surroundings drawn by the students are analysed via content analysis methodology. The studying pool of the research is formed from 6th graders from a school subordinated to Ministry of Education. The pool is chosen considering easiness of accessibility. Data is acquired via analysing of sketches spring from the students, who form the research pool; drawings consist of environmental components that students can remember about school and its surroundings and their ways to use to get home from school. The process of drawing sketch is repeated periodically; during the process, talks and discussions are held about their surroundings they live in, in order to improve students' perceptions of environment and recognize their surroundings. The gathered data is interpreted by taking into consideration the changes occurring in the sketches of students' during the process. After analysing of sketches formed during the process of study, it is understood that, there are significant changes among the students' perceptions of environment between the first and last application, in course of time they observe their surroundings in a more detailed manner and reflect their observations to sketches more intensely. Via the conducted evaluations it is observed that the perceptions of students about their environment are chanced and their fallacies about perceiving their environment are improved. Mind maps of students' school and surroundings have been assessed according to gender, academic achievement.
Keywords: Perception of environment; cognitive mapping; perception; secondary school